2020
DOI: 10.5324/fn.v40i0.3101
|View full text |Cite
|
Sign up to set email alerts
|

The freshwater shrimp Gammarus lacustris (Malacostraca, Amphipoda) in lakes on the Hardangervidda mountain plateau, southern Norway: distribution and environmental requirements

Abstract: The distribution of the amphipod Gammarus lacustris on the Hardangervidda mountain plateau was mapped by screening published data from 245 lakes in 11 and 16 catchments in western and central/eastern areas, respectively. These data are primarily based on stomach analyses of brown trout Salmo trutta. In central/eastern areas, G. lacustris was recorded in 79% of all the lakes examined, while there are only two former records (4%) in the western area. The distribution pattern of G. lacustris on Hardangervidda app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…This may be reinforced in high altitude lakes with even lower temperatures as documented in western areas. Thus, this small crustacean seems to be more viable in harsh conditions compared to L. arcticus and G. lacustris earlier reported from the same area (Qvenild & Hesthagen 2019;Qvenild et al 2020 Appendix 2. The catch of brown trout and the crustacean species Eurycercus lamellatus, Gammarus lacustris and Lepidurus arcticus in the 100 fishing events in the five study lakes (cf.…”
Section: Environmental Conditions May Limit the Distribution Of Eurycmentioning
confidence: 55%
See 1 more Smart Citation
“…This may be reinforced in high altitude lakes with even lower temperatures as documented in western areas. Thus, this small crustacean seems to be more viable in harsh conditions compared to L. arcticus and G. lacustris earlier reported from the same area (Qvenild & Hesthagen 2019;Qvenild et al 2020 Appendix 2. The catch of brown trout and the crustacean species Eurycercus lamellatus, Gammarus lacustris and Lepidurus arcticus in the 100 fishing events in the five study lakes (cf.…”
Section: Environmental Conditions May Limit the Distribution Of Eurycmentioning
confidence: 55%
“…To elucidate the ability of E. lamellatus to withstand high predation pressure from brown trout, we analysed their diet from five lakes at the central part of the plateau throughout the growing season for 15 years (see . In one of these lakes, been shown for L. arcticus (Qvenild & Hesthagen 2019) and G. lacustris (Qvenild et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Introduced freshwater fish and invertebrate species may restructure food webs and cause major ecological changes, often at the expense of local species (Langeland 1981;Lasenby et al 1986;Miller 1989;Spencer et al 1991;Kolar & Logde 2002;Baxter et al 2004). The crustaceans Gammarus lacustris G. O. Sars, 1863 and Lepidurus arcticus (Pallas, 1793) are among the most important food items for brown trout in lakes on Hardangervidda (L' Abée-Lund & Saegrov 1991;Borgstrøm 2016;Qvenild et al 2020), as well as in other mountain areas in southern Norway (Aass 1969;Lien 1978). European minnow feed on the same prey species (Borgstrøm et al 1985;Museth et al 2010), also indicated by the δ 15 N of the analysed European minnow from lake Skaupssjøen being nearly in the same range as found for brown trout in the analysed allopatric populations.…”
Section: Discussionmentioning
confidence: 99%